COVID 19: Dentistry related aspects - Hagar Alaa El-Naggar; Manal El-Nouaem; Nesrine Fayed (Academy Publishing Center, 2021)
The coronavirus disease 2019 (COVID-19) is a highly contagious transmittable disease caused by a recently discovered coronavirus, SARS-CoV-2. The COVID-19 is associated with a global "pandemic" health situation. In humans, the effects of SARS-CoV-2 range from flu (influenza) like symptoms to severe respiratory tract infections and sometimes death. Some oral manifestations associated with this virus have also been reported. This literature overview provides a description of pathophysiology, the clinical aspects of COVID-19 and its transmission. Because Sars-CoV-2 is highly infective through airborne contamination, dental professionals play great roles in the transmission of this virus in dental environment. In this review, we also discussed various preventive and control measures during dental practice to combat COVID-19 effectively. Furthermore, we described and highlighted the potential of tele dentistry as a new approach during the COVID-19 crisis.